INFLUENCE OF OPERATING PROFIT, NET PROFIT, AND PROFIT GROSS IN PREDICTING FUTURE CASH FLOWS IN FOOD COMPANIES AND DRINK LISTED IN THE IDX 2016 – 2018 - Kusuma, Indra Lila; Sumadi, Sumadi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of operating income, net income, gross profit in predicting future cash flows in food and beverage companies listed on the Indonesia Stock Exchange. The research used is a causal study with a population of food and beverage companies listed on the Indonesia Stock Exchange from 2016 to 2018. This study used a purposive sampling method with a sample of 19 companies which are food and beverage companies listed on the Indonesian stock exchange period 2016 - 2018. Data collection in this study was carried out using secondary data, namely the financial statements of food and beverage companies for the period 2016 - 2018, which were listed on the Indonesian stock exchange. The results of the study obtained partially from the operating profit variable affect the future cash flow while the net income variable and the gross profit variable have no partial effect on future cash flows. Simultaneously operating income, net profit, and gross profit affect the future cash flow and give an influence of 0.617 or 61.7% in predicting future cash flows. Keywords: Operating Profit, Net Profit, and Gross Profit, Cash Flow